Dystocia due to Schistosoma Reflexus and its Management through Fetotomy: A Case Report - Yadav, Hanuman P.; Shah, Nadeem; Kumar, Brijesh; Saxena , Atul (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
Schistosomus reflexus (SR) is seen most commonly in cattle, but is rare in sheep, goat and swine (Roberts et al., 1971). The highest prevalence of SR is believed to occur in cattle ranging from a low of 0.01% (Sloss and Johnston, 1967) to a high of 1.3% (Knight, 1996) of bovine dystocia. Such occurrences are costly to the cattle industry because of the reduction in the number of viable offspring, loss of milk production, infertility or prolonged inter-calving interval and expenses on management of dystocia. Schistosomus reflexus is a major congenital anomaly which occurs during embryonic development. The aetiology is unknown but it may be due to genetic factors, mutation, chromosomal anomalies, infectious agents and environmental factors or combination of all the factors (Ozsoy et al., 2009). The main defect is acute angulations of the vertebral column such that the tail lies close to the head. This fatal congenital syndrome is characterized by the presence of exposed abdominal and sometimes thoracic viscera (Noakes et al., 2002). The present case report describes dystocia due to schistosomus reflexus in a Hariana cow and its successful management through fetotomy.